Producción agroecológica de lechuga (Lactuca sativa L.) y pimiento (Capsicum annuum L.) con la aplicación de biofertilizantes resultado de la simbiosis Azolla anabaena y lixiviado de raquis de banano - Cordero Rojas, Fanny Katherine (2023)
Azolla is a floating aquatic fern that is easy to propagate and does not require complicated technologies and is within the reach of farmers. In order to contribute to family farming, it was proposed to produce nitrogen from the symbiosis Azolla filiculoides in accessible conditions to farmers in the cultivation of lettuce and bell pepper. The study was carried out in Santa Teresita parish, ¨Saca¨ farm, Espindola canton. Two experiments were implemented in randomized block designs with four replicates and four treatments: control; NitrAgua + Azolla filiculoides biomass; banana rachis leachate; liquefied Azolla filiculoides biomass + banana rachis leachate. The water characteristics after 30 days in the Azollario were: pH 7.38; average ambient temperature of 25 °C, maximum nitrogen content in the Azollario of 11.77 mg/l. The highest results obtained were with the application of the banana rachis leachate, for the lettuce crop of 24.1 cm plant height; 1.4 cm stem diameter, 27 leaves per plant and 210 g weight; for the bell pepper crop 159.3 cm plant height; 98 leaves per plant; 6 fruits per plant; 16.7 cm fruit length; 18.9 cm fruit diameter and 174.74 g weight. These results respond to the effectiveness of the biofertilizer, due to its high nutrient content that favors vigorous development and high-quality production. Keywords: azollario, NitrAgua, banana rachis leachate, biofertilizer, family farming, nitrogen.